2022
DOI: 10.1155/2022/9387583
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Perceived Vaccination on Students’ Online Learning Intentions: A Moderated Mediation Model

Abstract: The current study proposed and tested a moderated mediation model to reveal the effect of perceived vaccination (PV) on students’ online learning intentions (SOLI) during the COVID-19 pandemic. A questionnaire was distributed to 663 full- and part-time students at Vietnamese universities, and 632 responses were analyzed. SPSS 20 software and Hayes SPSS Process Macro (model 5) were used to test five hypotheses, all of which were supported. The study found that students’ online learning intentions decreased afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…en the correlation analysis is carried out. In this article, SPSS 19.0 [22,23] is used to test the correlation of each variable in the model, and the test results are shown in Table 4.…”
Section: Correlation Analysismentioning
confidence: 99%
“…en the correlation analysis is carried out. In this article, SPSS 19.0 [22,23] is used to test the correlation of each variable in the model, and the test results are shown in Table 4.…”
Section: Correlation Analysismentioning
confidence: 99%
“…This difference could be due to the changing pandemic situation and the growth in the vaccination rate. The current study was conducted when many people had received the COVID-19 vaccine, so although there was still a concern about the risk of infection in the workplace and the spread of the disease in the community, fears about the severity of COVID-19 decreased slightly once people had been vaccinated against it (Nong et al ., 2022), compared to the perceived vulnerability during the initial period.…”
Section: Discussionmentioning
confidence: 99%
“…Throughout the COVID-19 period, these policies and applications have unwittingly encouraged the introduction of the e-government in Vietnam. At the time of the present study, Vietnam is dealing with the fourth wave of COVID-19, with 1,084,625 cases reported (Nong et al ., 2022). Despite this, Vietnam may be praised for its management of the pandemic (Trevisan et al ., 2020).…”
Section: Literature Reviewmentioning
confidence: 98%